Trends in socioeconomic inequalities among adult male hardcore smokers in Vietnam: 2010-2015 - Vu Duy Kien; Tej Ram Jat; Kim Bao Giang; Phan Thi Hai; Doan Thi Thu Huyen; Luong Ngoc Khue; Nguyen Tuan Lam; Phan Thi Quynh Nga; Nguyen The Quan; Hoang Van Minh (BMC, 2017)
Abstract Background Despite male smokers being dominant in Vietnam, scarce evidence on trends in socioeconomics inequalities among the hardcore male smokers is available in the country. In this study, we aimed at assessing the trends in socioeconomics inequalities among the hardcore smokers in adult male population in Vietnam over a five-year period from 2010 to 2015. Methods We used data from two rounds of the Vietnam Global Adult Tobacco Survey (GATS) conducted in 2010 and 2015. We included only men aged 25 years and above in the analysis. We measured socioeconomic inequalities among hardcore smokers by calculating the concentration index. We conducted multiple logistic regression analysis to identify factors associated with hardcore smoking among men aged 25 years and above. Results The results of this study showed that the prevalence of male hardcore smokers aged 25 years and above in Vietnam was 9.5% in 2010 which increased to 13.1% in 2015. The prevalence of male hardcore smokers declined in the richest group from the 2010 level whereas it increased in the middle, poor and poorest groups. All values of weighted concentration indices indicated that the prevalence of male hardcore smokers occurred more among the poor men in Vietnam in both 2010 and 2015. The socioeconomic inequalities in hardcore smokers increased during 2010 and 2015. Residence in urban areas was significantly associated with higher adult male hardcore smoking in our study. Belonging to the age groups between 40 and 59 years, attaining primary and lower education, being self-employed, belonging to the poorest household group, smoking being allowed at home and no rule for smoking at home were associated with higher risk of being hardcore smoker among adult males in Vietnam. Conclusions We found increased trends in socioeconomic inequalities in hardcore smoking among the study population. Our study results indicate that existing smoking secession and tobacco control policy and interventions need to be modified or new policies and interventions should be introduced with the perspective of addressing socioeconomic inequalities to have the desired impact. We recommend implementing specific targeted interventions for vulnerable population groups for better results.